Polskie portale internetowe na Wyspach Brytyjskich - Brzoza, Katarzyna (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: The Polish web portals on the British Isles The aim of this study is to show the landscape of the Polish web portals on the British Isles and participation of the Internet network in maintaining relationships with the family house by the Polish emigration. At the moment, there are lots of portals to Polish migrants, and counting. The questionnaire surveys showed that the Internet is very important source of information about situation in the country for Poles who are abroad. Moreover, they can communicate with the family and friends who stayed in Poland by means of the Web. Key words: web portal, questionnaire surveys, Internet network, Polish emigration